2020
DOI: 10.3390/foods9121796
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Food Nutritional Labels Use in Nanjing, China

Abstract: A correct use of food nutrition la bels benefits consumers in pursuing balanced diets. As a result, we conducted interviews in Nanjing, China and randomly sampled 427 respondents. Further, we used both descriptive statistics and binary logistic regression to assess their perception of food nutrition label use. The results indicated that the current situation is not ideal in Nanjing. Only 7.26% of respondents use labeling consistently. Data on purchasing experience, comprehension, nutritional value, work sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This finding supports studies suggesting that parents check food labels to prevent their children from consuming unhealthy foods [ 49 ] and that nutrient claims have a stronger impact on mothers' perception of health and snack choices for their children compared to the nutrient content [ 50 ]. The findings from studies investigating the relationship between age and food label use are inconsistent [ 11 , 12 , 14 , 17 , 21 23 ]. In this study, using the ingredients list and claims were found to be related to older age, but reading the nutrition facts was not related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports studies suggesting that parents check food labels to prevent their children from consuming unhealthy foods [ 49 ] and that nutrient claims have a stronger impact on mothers' perception of health and snack choices for their children compared to the nutrient content [ 50 ]. The findings from studies investigating the relationship between age and food label use are inconsistent [ 11 , 12 , 14 , 17 , 21 23 ]. In this study, using the ingredients list and claims were found to be related to older age, but reading the nutrition facts was not related.…”
Section: Discussionmentioning
confidence: 99%
“…The use of food labels is associated with various health-related lifestyle habits. Having specific weight goals [ 11 ], diet awareness [ 17 ], and being physically active [ 11 , 23 ] were found to be more likely to lead to using food labels and nutrition fact panels. In line with these findings, the present study found that regular physical activity was associated with the likelihood of reading all sections of the food label, and dieting was related to using a nutrition facts panel and ingredients lists.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency towards healthier diets was confirmed also by Brihan et al [64] who conducted a study on Romanian consumers. Recently, consumers have paid more attention towards learning about the products and their nutritional facts [65,66], perhaps due to the information campaign through massmedia related to the benefits of healthy diets. Thus, it is not surprising that a significant amount of consumers expressed their concern related to the possibility to continue to buy from the same producers.…”
Section: Discussionmentioning
confidence: 99%
“…Primary food shoppers are more likely to use the NFP than those who are not. 13,26,27 Considering that they are highly involved in food selection and purchase, they have a higher chance of referring to the NFP than those who do not shop. Moreover, food shopping is primarily done by the head of the household, usually the parents.…”
Section: Factors Associated With Nfp Usementioning
confidence: 99%
“…In relation, being a primary household food shopper increases the frequency of NFP use. 13,26,27 Lastly, those diagnosed with disease or risk factors, 20,27,28 and with normal, obese, or overweight body mass index 9,16,19,22 were most likely to use the NFP.…”
Section: Introductionmentioning
confidence: 99%